Interaction of a genetic risk score with physical activity, physical inactivity, and body mass index in relation to venous thromboembolism risk. Issue 4 (8th March 2018) - Kim, Jihye; Kraft, Peter; Hagan, Kaitlin A.; Harrington, Laura B.; Lindstroem, Sara; Kabrhel, Christopher
ABSTRACT: Introduction: Venous thromboembolism (VTE) is highly heritable. Physical activity, physical inactivity and body mass index (BMI) are also risk factors, but evidence of interaction between genetic and environmental risk factors is limited. Methods: Data on 2, 134 VTE cases and 3, 890 matched controls were obtained from the Nurses' Health Study (NHS), Nurses' Health Study II (NHS II), and Health Professionals Follow‐up Study (HPFS). We calculated a weighted genetic risk score (wGRS) using 16 single nucleotide polymorphisms associated with VTE risk in published genome‐wide association studies (GWAS). Data on three risk factors, physical activity (metabolic equivalent [MET] hours per week), physical inactivity (sitting hours per week) and BMI, were obtained from biennial questionnaires. VTE cases were incident since cohort inception; controls were matched to cases on age, cohort, and genotype array. Using conditional logistic regression, we assessed joint effects and interaction effects on both additive and multiplicative scales. We also ran models using continuous wGRS stratified by risk‐factor categories. Results: We observed a supra‐additive interaction between wGRS and BMI. Having both high wGRS and high BMI was associated with a 3.4‐fold greater risk of VTE (relative excess risk due to interaction = 0.69, p = 0.046). However, we did not find evidence for a multiplicative interaction with BMI. No interactions were observed for physical activity or inactivity. Conclusion: We found a synergetic effect between a genetic risk score and high BMI on the risk of VTE. Intervention efforts lowering BMI to decrease VTE risk may have particularly large beneficial effects among individuals with high genetic risk.